CHEMICAL ANALYSIS OF THERMALLY AGED CABLES IN NUCLEAR POWER PLANTS - Pirc, Marko; Avsec, Jurij; Vrsaljko, Dijana (Journal of Energy Technology, 2025)
The paper presents findings on the implementation of various mechanical and chemical diagnostic procedures aimed at enhancing the monitoring of cable insulation conditions in Krško Nuclear Power Plant (NEK). This article introduces the advancement of four novel diagnostic testing methodologies for evaluating the mechanical and chemical properties of cable insulation: Indenter Modulus (IM), Differential Scanning Calorimetry (DSC), Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetric analysis (TGA) and X-Ray Fluorescence Spectral Analysis (XRF). Experiments were performed on diverse samples of widely used nuclear-qualified cable polymer materials, including Ethylene Propylene Rubber (EPR) and Crosslinked Polyethylene (XLPE), all with a Chlorosulphonated Polyethylene (CSPE) jacket. Samples from various vintages were subjected to additional temperature ageing in many stages, to establish field testing acceptability requirements and assess the remaining lifespan of the polymer insulation. Diagnostic tests were performed and some preliminary results are reported.